93.6k views
0 votes
Help please picture attached

Help please picture attached-example-1

2 Answers

4 votes

Answer:

0

Explanation:

Substitute x = 144 into the expression for f(x) - g(x)


√(144) + 12 - 2
√(144)

= 12 + 12 - (2 × 12)

= 12 + 12 - 24

= 0

User Niyamat Ullah
by
5.4k points
6 votes

Hello!

The answer is: The third option, 0.

Why?

We are asked to find (f-g) evaluated in 144, so the definition states that:


(f-g)(x)=f(x)-g(x)

So,


f(x)-g(x)=√(x) +12-2√(x)=-√(x) +12

We must remember that evaluating a function means replacing the variable with the given value, for this case it's 144.

Then, evaluating:


(f-g)(144)=-√(144)+12=-12+12=0

Hence, if:


(f-g)(144)=0

The correct option is the third option, 0.

Have a nice day!

User FredericJacobs
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.